2018
DOI: 10.1016/j.ijscr.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mesenteric desmoid tumors after gastrectomy for gastric cancer: A case report and literature review

Abstract: HighlightsA desmoid tumor often occurs at a surgical site of familial adenomatous polyposis.Multiple mesenteric desmoids could emerge after gastrectomy for gastric cancer.It is difficult to differentiate mesenteric desmoids from a cancer recurrence.Surgical resection of the tumors is a useful option as a diagnostic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Tumour markers (CEA, CA 19-9 and CA 125) were measured in the preoperative work-up of these five patients. All were within the normal range, consistent with previous reports [36,37]. In contrast, Okamura et al [35] reported a rise in CEA above the normal range for 27 months post gastrectomy for gastric cancer where a recurrence was suspected, but despite this rise in CEA and the increased PET uptake the lesion was proven histologically to be consistent with fibromatosis.…”
Section: Both Nodules Avidsupporting
confidence: 88%
See 4 more Smart Citations
“…Tumour markers (CEA, CA 19-9 and CA 125) were measured in the preoperative work-up of these five patients. All were within the normal range, consistent with previous reports [36,37]. In contrast, Okamura et al [35] reported a rise in CEA above the normal range for 27 months post gastrectomy for gastric cancer where a recurrence was suspected, but despite this rise in CEA and the increased PET uptake the lesion was proven histologically to be consistent with fibromatosis.…”
Section: Both Nodules Avidsupporting
confidence: 88%
“…Makis et al [43] have previously reported a desmoid tumour of the ascending colon as PET avid on preoperative work-up, raising a strong suspicion of malignancy and therefore directing decision to proceed with right hemicolectomy. Similarly, Yamamoto et al [37] have reported lesions in which increased PET uptake was concerning for tumour recurrence post gastrectomy for gastric cancer, but subsequent histology demonstrated that the lesions were consistent with fibromatosis. On the other hand, Mizuno et al [7] do not report tumour marker testing or PET scanning in their preoperative work-up for a soft tissue mass suggesting colon cancer recurrence on serial CT surveillance scans.…”
Section: Both Nodules Avidmentioning
confidence: 89%
See 3 more Smart Citations